The Impact of Human Security and Terrorism on Nigeria Economy: A Case of Insurgency - Farid Illo; Muslim Diekola Akanmu; Nazariah Osman (Muhammadiyah University Press, 2023)
Globally, terrorism has become a major threat to the national security of many nations as it directly affects economic, political, and social welfare. The recent development in security studies has led to the emergence of a new concept called “human security” which focuses on an individual’s safety in a country. To date, Nigeria still experiences security challenges at the hand of Boko Haram, a terrorist sect with the agenda to impose Sharia law on secular Nigerians. Therefore, this research investigated the impact of the Boko Haram insurgency in Nigeria on human security. To accomplish this objective, responses were collected through a qualitative approach using in-depth interviews. Findings indicate that the terror activities of Boko Haram have led to the death of thousands of lives, loss of properties, shortage of food supply, and an increase in number of internally displaced people in the affected regions. Also, the study revealed that education has been drastically affected and small businesses have collapsed, thus increasing the poverty level in the country. The paper concluded that the insurgency has an adverse effect on indispensable factors that constitute human security such as health, education, food and nutrition, small business enterprises, and human rights and liberty.